International Trade and Supply Shortage with Effect of Covid 19 Pandemic: Evidence from Developing Countries - Mangane, Mahamadou (Eastern Mediterranean University, 2023)
As the recent coronavirus (COVID-19) outbreak demonstrates, pandemics and epidemics may wreak havoc on supply chains (SC) on a global scale. Activities all around the globe were impacted by the Coronavirus pandemic, but supply chain (SC) disruptions were most noticeable. The supply chain is not likely to recover to its pre COVID-19 state, and the effect on firms is predicted to last forever. This research looks at how the COVID-19 epidemic has affected supply chains in underdeveloped countries, including the problems it has caused, the obstacles it has presented, and the overall trend. This thesis employs empirical analysis in the form of Pearson correlation, pooled OLS, a fixed effects model, and a random effects model to evaluate the variables that influence supply chain in the selected developing nations between the year 2015 and 2021. GDP is used as a proxy for supply chain shortfall as the dependent variable whereas the rest of the variables are used as the explanatory variables such as government debt (DEBT), total trade (TRADE2), imports of goods and services (TTRADE), and growth in the labor force (LABGROWTH). The empirical results show that debt, imports of goods and services, dummy variable and labor force have impact on economic growth whilst supply chain has no influence on economic growth. Keywords: supply chain, covid-19, developing countries, disruption, manufacturing industries, pooled OLS, a fixed effects model, a random effects model.

Son koronavirüs (COVID-19) salgınının gösterdiği gibi, pandemiler ve salgınlar küresel ölçekte tedarik zincirlerine (SC) zarar verebilir. Dünyanın dört bir yanındaki faaliyetler, Coronavirüs pandemisinden etkilendi, ancak en çok tedarik zinciri (SC) kesintileri göze çarpıyordu. Tedarik zincirinin COVID-19 öncesi durumuna gelmesi pek olası değil ve bunun firmalar üzerindeki etkisinin sonsuza kadar süreceği tahmin ediliyor. Bu tez, COVID-19 salgınının az gelişmiş ülkelerde tedarik zincirlerini, neden olduğu sorunlar, sunduğu engeller ve genel eğilim dahil olmak üzere nasıl etkilediğine bakıyor. Bu tez, gelişmekte olan ülkelerde tedarik zincirini etkileyen değişkenleri değerlendirmek için Pearson korelasyonu, küçük kareler yöntemi, sabit etkiler modeli ve rastgele etkiler modeli şeklinde ampirik analiz kullanır. GSYİH, bağımlı değişken olarak tedarik zinciri açığı için kullanılırken, değişkenlerin geri kalanı, devlet borcu, toplam ticaret, mal-hizmet ithalatı ve işgücündeki büyüme değişkenler ise bağımsız değişken olarak kullanılır. Ampirik sonuçlar, borç, mal ve hizmet ithalatı ve işgücündeki büyümenin ayrıca aylak değişkenin ekonomik büyüme üzerinde etkisi olduğunu, tedarik zincirinin ise ekonomik büyüme üzerinde etkisinin olmadığını göstermektedir. Anahtar Kelimeler: tedarik zinciri, covid-19, gelişmekte olan ülkeler bozulma, üretim endüstrileri, küçük kareler yöntemi, sabit etkiler modeli ve rastgele etkiler model.
Master of Business Administration. Institute of Graduate Studies and Research. Thesis (M.B.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2023. Supervisor: Prof. Dr. Sami Fethi
Keywords: Thesis Tez; International Trade--Covid 19 Pandemic; Supply chain; covid-19; developing countries; disruption; manufacturing industries; pooled OLS; a fixed effects model; a random effects model